2015
DOI: 10.1371/journal.pone.0118708
|View full text |Cite
|
Sign up to set email alerts
|

The Sound and the Fury—Bees Hiss when Expecting Danger

Abstract: Honey bees are important model systems for the investigation of learning and memory and for a better understanding of the neuronal basics of brain function. Honey bees also possess a rich repertoire of tones and sounds, from queen piping and quacking to worker hissing and buzzing. In this study, we tested whether the worker bees’ sounds can be used as a measure of learning. We therefore conditioned honey bees aversively to odours in a walking arena and recorded both their sound production and their movement. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…Our results show that A. cerana japonica clearly hiss during the daytime, and that the start and end of the hiss is adjusted to the timing of sunrise and sunset. This result was also interesting, since the hissing behavior of honey bees is typically regarded as an aposematic signal acting as a conditional reflex behavior against disturbance, as reported in many other bees (Wehmann et al 2015). Considering our results, it is likely that there are other potential functions or, at least, unknown characteristics, of the hissing behavior of A. cerana japonica .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results show that A. cerana japonica clearly hiss during the daytime, and that the start and end of the hiss is adjusted to the timing of sunrise and sunset. This result was also interesting, since the hissing behavior of honey bees is typically regarded as an aposematic signal acting as a conditional reflex behavior against disturbance, as reported in many other bees (Wehmann et al 2015). Considering our results, it is likely that there are other potential functions or, at least, unknown characteristics, of the hissing behavior of A. cerana japonica .…”
Section: Discussionsupporting
confidence: 72%
“…Regarding the function of hissing, it is thought to serve as an aposematic signal in response to disturbances, such as physical disturbance of a colony or the approach of predator, such as hornets (Fuchs and Koeniger 1974;Sarma et al 2002;Hrncir et al 2005;Fuchs and Tautz 2011;Wehmann et al 2015); a correlation formed on the basis of circumstantial and observational evidence over time. However, findings from the previous study (Kawakita et al 2018) showed that A. cerana japonica could hiss even without an obvious disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Hissing seems to be an innate response to noxious stimuli, as this behaviour is also produced in response to electric shocks (Wehmann et al, 2015). Whether these sounds are used as an alarm signal to the colony, as a threat to hornets (which are known to use high-frequency sounds for communication) or are just distress sounds remains to be determined.…”
Section: Defence Against Other Insectsmentioning
confidence: 99%
“…This system was an adapted version of the one used for aversive olfactory conditioning (Kirkerud et al, 2013; Schott et al, 2015; Wehmann et al, 2015). In the APIS assay bees are able to move freely in a conditioning chamber, which is equipped with LEDs to provide visual stimuli of different wavelengths and intensities.…”
Section: Introductionmentioning
confidence: 99%